Penerapan Metode POQ Dalam Penentuan Persediaan Material Proyek pada PT. Swakarya Putra Berbasis Android - Ginting, Daniel; Rika Rosnelly (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Material inventory is a crucial factor in the smooth running of construction projects. PT. Swakarya Putra has been facing challenges in managing its inventory, such as delays in stock information, recording errors, and unplanned purchases. The purpose of implementing the POQ method is to control material inventory to minimize inventory costs and ensure timely material availability. The POQ method contributes to determining the optimal order quantity and timing by considering ordering, storage costs, and project material requirements. The system is built on an Android platform so that it can be accessed in real time by relevant parties in the field. The implementation results indicate that the system is able to calculate material ordering schedules accurately, simplify stock monitoring, and reduce the risk of shortages or excess inventory. Thus, the implementation of the Android-based POQ method can improve the efficiency of controlling project material inventory at PT. Swakarya Putra. This method helps minimize the risk of stockouts and excess stock, as well as improve operational efficiency by ordering quantities at specific time intervals.